Divine attributes : knowing the covenantal God of scripture - Peckham, John C., 1981- (Grand Rapids, Michigan : : Baker Academic, a division of Baker Publishing Group, 2021)
"Offers a clear and constructive account of the nature and attributes of God, bringing the biblical portrayal of God in relationship to the world into dialogue with prominent philosophical and theological questions"--
Includes bibliographical references (pages 269-294) and indexes.
Keywords: God (Christianity) -- Attributes